Effect of Certain Litter Materials on Broiler Performance - Sini Thomas (Department of Paultry Science, College of Veterinary and Animal Sciences, 1999)
An experiment was designed and conducted at the Department of poultry Science, College of Veterinary and Animal Sciences, Mannuthy to evaluate the efficacy of different litter materials on the performance of broilers under hot-humid conditions of Kerala. Two hundred and ten, one-day old straight-run commerical broiler chicks were reared for a period of eight weeks. The birds were allotted into five different litter treatment groups, V1Z., wood shavings (T1) which formed the control group, saw dust (T2), rice husk (T3), coir pith (T4) and paddy chaff (T5), each c0mprising of three replicates with fourteen birds each. Standard broiler starter and finisher rations were formulated as per BIS (1992) specifications for the broilers. The chicks were reared under standard managemental conditions up to eight weeks of age. Results of the study revealed that body weight and body weight gain were not influenced by different litter treatments throughout the experimental period. Even though feed consumption and feed efficiency were influenced by litter materials during the initial periods, there was no impact for the rest of the experimental period. Processing yields and losses were not affected by different litter treatments. Litter quality parameters like weight of the litter at the beginning and end of the experiment, weekly moisture content,